Antibacterial resistance in dermatology: a modern perspective on the problem and the place of amoxicillin/clavulanic acid in the treatment of bacterial skin infections - E.V. Svechnikova; S.E. Zhufina (Russian Journal of Clinical Dermatology and Venereology, 2026)
Introduction. The problem of microbial resistance to antibacterial drugs is becoming increasingly pressing each year and poses a global threat to public health. In dermatological practice, systemic antibiotics are widely used for both skin and soft tissue infections and chronic inflammatory dermatoses (acne, rosacea, hidradenitis suppurativa), which increases the risk of resistant strain selection and microbiome disruption. Objective. To analyze current literature data and our own clinical observations, as well as to substantiate the rational choice of antibacterial therapy in dermatology, with an emphasis on the efficacy and safety of dispersible amoxicillin/clavulanic acid. Material and methods. A review of the 2020—2025 literature on antibiotic resistance in dermatology and the use of amoxicillin/clavulanate was performed. In addition, two clinical cases (a 17-year-old patient with facial pyoderma and a 46-year-old patient with late acne complicated by pyoderma) are presented to demonstrate the drug’s efficacy in clinical practice. Results. The prevalence of MRSA in skin and soft tissue infections varies from 29% to 52% depending on the region. Furthermore, increasing resistance to fusidic acid and macrolides limits the choice of topical and systemic therapies. The combination of amoxicillin and clavulanic acid maintains activity against most clinically significant pathogens, including S. aureus and S. pyogenes. The dispersible formulation ensures high bioavailability, stable pharmacokinetics (including that of clavulanic acid), good tolerability, and ease of use, which increases adherence to therapy. In both clinical cases, complete regression of the lesions was achieved after a 7-day course of treatment with the drug. Conclusion. The combination of amoxicillin and clavulanic acid in dispersible tablets is an effective and safe treatment for bacterial skin infections, and its rational use helps curb antibiotic resistance in dermatological practice.